Profil keterampilan berpikir kreatif peserta didik dalam pembelajaran ipa kelas v di sekolah dasar - Titis Arum Widiastuti; Idam Ragil Widianto Atmojo; Dwi Yuniasih Saputri (Didaktika Dwija Indria, 2021)
This qualitative research was undertaken to describe about profile of students creativity thinking skill in natural science of V.3th grade students in SDN Mangkubumen Lor No. 15 Surakarta. The subject that used in this research were 6 students who selected by using purposive sampling. The methods data collection of this research used tests and interviews. Creativity thinking skill aspects include fluency, flexibility, and originality. The results of this research showes that the profile of creativity thinking skill at SDN Mangkubumen Lor No.15  in the creative criteria. Percentage of the profile of creativity thinking skill of V.3th grade in SDN Mangkubumen Lor No. 15 at 77,59%. This is the percentages for each indikator of creativity thinking skill. The percentage of fluency obtained 83.33%. The indicator of flexibility obtained 77.78%. And in the originality indicator obtained 66.67%. The most dominant indicator is fluency. Creative thinking skills are important for every students, so teachers must be able to develop their creativity thinking skill.